2017
DOI: 10.1063/1.5008493
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically enhanced closed-loop multi-turn sensor devices that enable reliable magnetic domain wall motion

Abstract: We experimentally realize a sophisticated structure geometry for reliable magnetic domain wall-based multiturn-counting sensor devices, which we term closed-loop devices that can sense millions of turns. The concept relies on the reliable propagation of domain walls through a cross-shaped intersection of magnetic conduits, to allow the intertwining of loops of the sensor device. As a key step to reach the necessary reliability of the operation, we develop a combination of tilted wires called the syphon structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…As a proof of concept, using a special design with a polyimide insulating layer attached to the surface of a silicon rod, a portable turn counter has been obtained, whose mechanism is in contrast to the common magnetic turn-counting sensors. [42][43][44] The wind driven semiconductor electricity generator has also been used to drive a graphene photodetector, which exhibits responsivity of over 35.8 A W À1 . This demonstrates a potential method for direct power supply for driving widely distributed sensors in the age of the IoTs.…”
Section: Introductionmentioning
confidence: 99%
“…As a proof of concept, using a special design with a polyimide insulating layer attached to the surface of a silicon rod, a portable turn counter has been obtained, whose mechanism is in contrast to the common magnetic turn-counting sensors. [42][43][44] The wind driven semiconductor electricity generator has also been used to drive a graphene photodetector, which exhibits responsivity of over 35.8 A W À1 . This demonstrates a potential method for direct power supply for driving widely distributed sensors in the age of the IoTs.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral magnets [1][2][3][4][5][6][7][8] have been investigated intensively in the last years due to their fascinating physical concepts and potential use in applications including sensors [9][10][11], logic [12][13][14], and magnetic memory devices [15,16]. Among different magnetic structures, domain walls [17], vortices [18], and skyrmions [19] have been investigated both theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…This intense research has enabled the use of DWs in memory devices 3 and magnetic sensors 4 . For example, a DW can be used to carry information about the angular position of an object and to count the number of rotations performed in a nonvolatile way [5][6][7] . The interest of magnetic sensors based on DWs is in their stability, making their non-volatile positioning suitable to many applications.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, uncontrolled nucleation of domain walls at higher fields needs to be avoided, thus setting the maximum operation field value. Previous studies about DW sensors investigated the propagation and nucleation fields, and showed how they depend on material parameters and device geometry [7][8][9][10][11][12] . While the field operation window in idealized operation conditions is known, in real devices further factors play a role and have been previously neglected.…”
Section: Introductionmentioning
confidence: 99%